Lessons after dark - Cooper, Isabel (Naperville, Ill. : Sourcebooks Casablanca, 2012)
"Olivia Brightmore didn't know what to expect when she took a position to teach at Englefiend School, an academy for 'gifted' children. But it wasn't having to rescue a young girl who levitated to the ceiling. Or battling a dark mystery in the surrounding woods. And nothing could have prepared her for Dr. Gareth St. John. He knew all about her history and scrutinized her every move because of it. But there was more than suspicion lurking in those luscious green eyes. Even with all the strange occurrences at the school, the most unsettling of all is the attraction pulling Olivia and Gareth together with a force that cannot be denied"--P. [4] of cover.
Keywords: Women teachers -- Fiction; Teachers of gifted children -- Fiction; Boarding schools -- Fiction; Man-woman relationships -- Fiction; Paranormal romance stories; Love stories